On the rate of convergence in the invariance principle for weakly dependent random variables - Mukhamedov, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 519.21 We consider nonstationary sequences of φ-mixing random variables. By using the Levy–Prokhorov distance, we estimate the rate of convergence in the invariance principle for nonstationary φ-mixing random variables. The obtained results extend and generalize several known results for nonstationary φ-mixing random variables.